Hepatotoxicity following systemic therapy for colorectal liver metastases and the impact of chemotherapy-associated liver injury on outcomes after curative liver resection. Issue 9 (September 2017) - Duwe, G.; Knitter, S.; Pesthy, S.; Beierle, A.S.; Bahra, M.; Schmelzle, M.; Schmuck, R.B.; Lohneis, P.; Raschzok, N.; Öllinger, R.; Sinn, M.; Struecker, B.; et al.
Abstract: Patients with colorectal liver metastases (CLM) have remarkably benefited from the advances in medical multimodal treatment and surgical techniques over the last two decades leading to significant improvements in long-term survival. More patients are currently undergoing liver resection following neoadjuvant chemotherapy, which has been increasingly established within the framework of curative-indented treatment strategies. However, the use of several cytotoxic agents has been linked to specific liver injuries that not only impair the ability of liver tissue to regenerate but also decrease long-term survival. One of the most common agents included in modern chemotherapy regimens is oxaliplatin, which is considered to induce a parenchymal damage of the liver primarily involving the sinusoids defined as sinusoidal obstruction syndrome (SOS). Administration of bevacizumab, an inhibitor of vascular endothelial growth factor (VEGF), has been reported to improve response of CLM to chemotherapy in clinical studies, concomitantly protecting the liver from the development of SOS. In this review, we aim to summarize current data on multimodal treatment concepts for CLM, give an in-depth overview of liver damage caused by cytostatic agents focusing on oxaliplatin-induced SOS, and evaluate the role of bevacizumab to improve clinical outcomes of patients with CLM and to protect the liver from the development of SOS.